A study on low-cost model of hospital pharmacy at a government healthcare teaching institute, as a feedforward measure of control - Rajesh Harsvardhan; Ruchi Kushwaha; Rakesh Gupta (Journal of Indira Gandhi Institute of Medical Sciences, 2022)
Introduction: There are very few government institutes that have “Hospital Supply Chain Management” of drugs and medicines, surgical goods, vendor-managed inventory, and outsourcing of patient care and services. Instead, they continue to have traditional Store and Purchase and Accounts departments and have often failed to appreciate the power of “Business Process Re-engineering.” The traditional Store and Purchase and Accounts departments are not able to encounter the new age “Challenges and Opportunities” and are entirely dependent on funds from the government to procure medicines and consumables. Methodology: A prospective analytical study was conducted from May 2021 to October 2021 at Hospital Pharmacy at a Government Healthcare Teaching Institute, wherein frequently prescribed antibiotics, whose multidrug resistance-associated protein was very high and patient needs to procure from outside medical stores were procured directly from the pharma companies through the rate contracts instead of local vendors. Further, these antibiotics were kept at hospital pharmacy for sale by applying minimal surcharges up to maximum of 10% of the purchased price and patients were requested to procure from it rather than outside pharmacy. Results: Over the duration of 4 months, it was observed that revenue generated per month for the hospital pharmacy was between INR 8000/- and 14,000/- but at the same time, there was a remarkable reduction in out-of-pocket expenditure (OOE) of the patient, between INR 63,000/- and 2 Lakhs and there was more satisfaction among patients. Conclusions: Based on the results, it can be safely concluded that it is the need of the hour for the government-funded hospitals to make a shift from the conventional system of procurement to this self-sustainable model of procurement. It will not only enable the hospital to be financially independent by reducing the need for budgetary support from the government but will also reduce the OOE of the patients leading to more satisfaction among them.